2019
DOI: 10.3390/cryst9020084
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on Homogeneous Melting of Benzene Phase I

Abstract: Molecular-dynamics simulations are used for examining the microscopic details of the homogeneous melting of benzene phase I. The equilibrium melting temperatures of our model were initially determined using the direct-coexistence method. Homogeneous melting at a higher temperature is achieved by heating a defect-and surfacefree crystal. The temperature-dependent potential energy and lattice parameters do not indicate a premelting phase even under superheated conditions. Further, statistical analyses using indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…These results indicate that all molecules change the orientations in the transition from phase I to the metastable phase. In the previous study, we have shown that at ambient pressure the flipping motion played an important role in the formation of the critical nucleus [32]. Hence, the rotational motion triggers the melting transition of phase I at both the pressures.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…These results indicate that all molecules change the orientations in the transition from phase I to the metastable phase. In the previous study, we have shown that at ambient pressure the flipping motion played an important role in the formation of the critical nucleus [32]. Hence, the rotational motion triggers the melting transition of phase I at both the pressures.…”
Section: Resultsmentioning
confidence: 84%
“…This premelting stage was later disproven by the investigation over the complete temperature range of 4 to 280 K [31]. Very recently, we performed the molecular dynamics (MD) simulations for the homogeneous melting of benzene phase I crystal near the limit of superheating and statistically demonstrated that there is no intermediate transient state between the crystal and liquid phases [32]. While these studies have been conducted under ambient pressure, the melting dynamics under high pressure have not been explored.…”
Section: Introductionmentioning
confidence: 99%